2015
DOI: 10.12693/aphyspola.127.505
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Doped Zigzag Silicene Nanoribbons

Abstract: Thermoelectric properties of silicene nanoribbons doped with magnetic impurity atoms are investigated theoretically for both antiparallel and parallel orientations of the edge magnetic moments. Spin density distribution and transport parameters have been determined by ab-initio numerical methods based on the density functional theory. Doping with magnetic atoms considerably modies the spin density distribution, leading to a ground state with a non-zero magnetic moment. Apart from this, the spin thermopower can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Thermoelectric figure of merit (FOM) upto 160 are achieved in silicene provided the fermi energy is located approximately 100 meV [25]. Zberecki et al [26] shown spin thermopower in silicene can be considerably enhanced by the impurity atoms. The mobility of carriers are calculated as a function of temperature and compared with the experimental results [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric figure of merit (FOM) upto 160 are achieved in silicene provided the fermi energy is located approximately 100 meV [25]. Zberecki et al [26] shown spin thermopower in silicene can be considerably enhanced by the impurity atoms. The mobility of carriers are calculated as a function of temperature and compared with the experimental results [27].…”
Section: Introductionmentioning
confidence: 99%